(untitled) (FUDMA JOURNAL OF SCIENCES, 2023)
Schistosomiasis is largely a water-snail related disease that mostly affects school aged children in developing countries. The disease is also related to poverty and lack of health education among other factors. The study focused on the urine associated schistosomiasis in Dawakin Kudu Local Government Area, Kano state. Two hundred and twenty seven (227) urine samples were collected and processed using standard methods, which include macroscopy for colour, turbidity and any blood tinge and microscopy, in which the urine samples were centrifuged and the sediments examined using 10x and 40x objectives with condenser closed sufficiently to give contrast. In the results, overall prevalence rate obtained was 19.4%. According to gender, the result of Schistosoma haematobium infestation in the five villages revealed that, infection was found only among males 44(25.7%) while females had 0(0.00%). Prevalence according to localities indicated, 24(54.5%) for Tsakuwa, 7(15.9%) for Yan Barau, and 13(29.6%) for Yaburawa while Kore and Dawaki had zero prevalence. Based on the result obtained, infection rate was higher among individuals in the age bracket of 9-12, with (50.0%) prevalence rate. It can be concluded from the result that, males are more at risk of urinary schistosomiasis than females among school aged children in the study area